2021
DOI: 10.1007/s00122-021-03780-8
|View full text |Cite
|
Sign up to set email alerts
|

Major locus for spontaneous haploid genome doubling detected by a case–control GWAS in exotic maize germplasm

Abstract: Major locus for spontaneous haploid genome doubling detected by a case-control GWAS in exotic maize germplasm Key messageA major locus for spontaneous haploid genome doubling was detected by a case-control GWAS in an exotic maize germplasm. The combination of double haploid breeding method with this locus leads to segregation distortion on genomic regions of chromosome five.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Absence of significant differences between BS39xA427_DH and BS39xA427_SSD lines for all traits in individual environments or across locations (Tables 2 and 3) suggest that spontaneous haploid genome doubling was not associated with undesirable linkage drag effects. Verzegnazzi et al (2021) found a significant enrichment of the A427 haplotype in the spontaneous haploid genome doubling QTL region on chromosome 5, which is consistent with strong selection for the major spontaneous haploid genome doubling QTL from A427 (Ren et al 2020;Trampe et al 2020) in this region.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Absence of significant differences between BS39xA427_DH and BS39xA427_SSD lines for all traits in individual environments or across locations (Tables 2 and 3) suggest that spontaneous haploid genome doubling was not associated with undesirable linkage drag effects. Verzegnazzi et al (2021) found a significant enrichment of the A427 haplotype in the spontaneous haploid genome doubling QTL region on chromosome 5, which is consistent with strong selection for the major spontaneous haploid genome doubling QTL from A427 (Ren et al 2020;Trampe et al 2020) in this region.…”
supporting
confidence: 69%
“…This may lead to selection and perhaps fixation of particular 383 haplotypes in genome regions contributing to DH line development, and thus narrow the diversity among DH lines compared to SSD lines. Based on allele frequencies, genetic differentiation, and heterozygosity, Verzegnazzi et al (2021) showed that both SSD and DH breeding methods capture most of the genetic variability present in the BS39 population.…”
mentioning
confidence: 99%
“…If so, this represents a remarkable case of parallel evolution of regulatory sequences [45][46][47] . Although both species are within the Cichorioideae subfamily of the Asteraceae, they occur in different subtribes that split between 13.5 and 20.8 million years ago 30,34 . They also differ fundamentally in the way female meiosis is avoided to achieve functional apomixis (Supplementary Note 1).…”
Section: Discussionmentioning
confidence: 99%
“…The observed twin seedlings grew slowly and either they died before true leaf formation, or those that did finally form true leaves were diploid. These diploid twins could be of sexual or parthenogenetic origin, in the latter case followed by spontaneous haploid genome doubling, which is often observed in crop species 34 .…”
Section: Functional Evidence That Par Induces Parthenogenesismentioning
confidence: 99%
“…Compared to linkage maps, the use of GWAS methodologies has advantages such as using genetically diverse populations with different rates of recombination and linkage disequilibrium (LD; Myles et al, 2009). Despite the observed GWAS efficiency in several crops (Warraich et al, 2020;Zhang et al, 2020;Verzegnazzi et al, 2021), this methodology still presents limitations related to the low proportion of phenotypic variance explained by the identified genomic regions (Manolio et al, 2009). As an alternative, the combination of GWAS results with other molecular methodologies, such as transcriptomics and proteomics analyses, can contribute to better knowledge of the genetic mechanisms involved in the definition of a trait (Tam et al, 2019), overcoming the statistical limitations on the characterization of a broad set of causal genomic regions.…”
Section: Introductionmentioning
confidence: 99%